Augmented Reality for Browsing Physical Collections in Academic Libraries. - Lund, Brady D.; Agbaji, Daniel A. (Public Services Quarterly)
Column description. The Future Voices in Public Services column is a forum for graduate students in library and information science programs to discuss key issues in academic library public services, to envision what they feel librarians in public service have to offer to academia, to tell us their visions for the profession, or to share research being conducted in library schools. We hope to provide fresh perspectives from those entering our field, in both the United States and other countries. Interested students in library and information science programs are invited to contact Miriam L. Matteson, mmattes1@kent.edu. Integrating emerging technology into existing library architecture is a challenge for organizations and further so for those with limited funds. Mobile technologies such as augmented reality provide a medium through which technology may be integrated at low or no cost to the organization. By employing augmented reality in searching physical collections of a library, patrons are provided a new means to engage with resources and library staff. Augmented reality is simple to use, inexpensive, and an exciting way to re-envision libraries beyond physical boundaries.